A Case Study of International Students’ Social Adjustment, Friendship Development, and Physical Activity - Li, Shuang; Zizzi, Sam (Journal of International Students, 2018)
Previous literature has focused on international student’s social transition and monocultural and bicultural ties. Little research has explored international students’ multicultural friendship development and the role that physical activity plays in their social interaction. The current case study explored a group of international students’ friendship development and the social aspect of physical activity. Data from individual interviews (pre and post), and 5 months of participant observations was used to describe two female international students’ experiences. Results suggested international students faced both language and cultural barriers in their social interactions with American students. Engagement in physical activities served as the context where observations of peer-to-peer social behaviors happened. Researchers argued that the multicultural friendship developed and strengthened by engaging in these physical activities. This paper also discussed implications and limitations of the study as well as future recommendations.